Assessing Nigerian Pre-Service Teachers’ Inclusive Education Pedagogical Knowledge (Journal of Guidance and Counselling Studies, 2025)
This study aimed at assessing pre-service teachers’ inclusive education pedagogical knowledge. One hundred thirteen pre-service teachers who had completed their teaching practice in two colleges of education in Zamfara State, Nigeria were sampled for the study. The descriptive survey research design was employed in the study. The data collection instrument consisted of a 49-item cognitive assessment scale designed in a true or false format. Data were analyzed using frequencies and percentages. Results revealed that participants had good understanding of the dimensions of inclusive pedagogical content knowledge but showed a lower understanding in areas like assistive technologies, collaborative strategies, and flexible instructional approaches. It was concluded that there is a positive impact of curriculum and policy reforms in colleges of education, as evidenced by the participants’ reported knowledge. Nonetheless, gaps in specific areas of knowledge highlight the need for further strengthening of the teacher education curriculum to ensure comprehensive preparation for inclusive teaching. Recommendations were made for the improvement of the teacher curriculum in colleges of education.